Registration of 'Rollag' Spring Wheat. Issue 2 (27th March 2015) - Anderson, J. A.; Wiersma, J. J.; Linkert, G. L.; Reynolds, S.; Kolmer, J. A.; Jin, Y.; Dill-Macky, R.; Hareland, G. A.
Abstract : Fusarium head blight (FHB) (caused primarily by Fusarium graminearum Schwabe) is a disease that annually threatens wheat ( Triticum aestivum L.) grown in the northern plains of the United States. Resistance to this disease is a high priority trait in the University of Minnesota's spring wheat breeding program. We utilized marker‐assisted selection in the F6 (pre‐yield trial stage) generation to identify lines containing Fhb1, a major quantitative trait locus for FHB resistance. One line, tested as MN05214‐3 in Minnesota statewide yield trials from 2008 to 2010 and in the Uniform Hard Red Spring Wheat Regional Nursery in 2009 and 2010, was released as 'Rollag' (Reg. No. CV‐1107, PI 665250) by the University of Minnesota Agricultural Experiment Station in 2011. Rollag is a mid‐maturity, semidwarf cultivar that has above‐average grain protein content. Rollag was released on the basis of its good resistance to FHB, resistance to lodging, competitive grain yield and acceptable end‐use quality characteristics. Rollag is well adapted to hard red spring wheat growing regions in Minnesota and the Upper Midwest.